Flexural Behavior of Simply Supported Beams Consisting of Gradient Concrete and GFRP Bars - Ji, Jing; Zhang, Runbao; Yu, Chenyu; He, Lingjie; Ren, Hongguo; Jiang, Liangqin (Frontiers in Materials, 2021)
In order to study the flexural behavior of simply-supported beams consisting of gradient concrete and GFRP bars, 28 simply-supported beams were designed. The main parameters included the strength grades of high-strength concrete (HSC), GFRP reinforcement ratio and sectional height of HSC. Based on nonlinear constitutive models of materials, meanwhile, considering the bond slip between concrete and GFRP bars, 5 simply-supported beams with gradient concrete and 5 simply-supported beams with GFRP bars were simulated respectively. Then the mid-span load -displacement curves of beams were obtained. By comparing with the experimental data, the rationality of material constitutive models and finite element modeling was verified. Based on this, the parameter analysis of the beams with GFRP bars and gradient concrete was carried out, and the failure modes of the beams were obtained through investigation. The results show that the failure process of the beams can be divided into two stages: elastic stage and working stage with cracks. With the increase of GFRP reinforcement ratio, the flexural bearing capacity of the beams does not change significantly, while their stiffness increases gradually. The flexural bearing capacity of the beams can be significantly improved by appropriately increasing the strength and sectional height of HSC. The ultimate bearing capacity of the beams is 40% higher than that of the GFRP concrete beams. Finally, based on the plane-section assumption, the calculation formula of normal-section flexural bearing capacity of this kind of beams is proposed through statistical regression method.